Characterization of magnetic actuators by measuring of magnetic stray fields with GMR-sensors - Brela, Matthäus; Kassim, Najdet; Franke, Jörg (2013 3rd International Electric Drives Production Conference, EDPC 2013 - Proceedings, 2013)
Common defects in electromagnetic actuators due to manufacturing are heterogeneous magnetic properties of materials, cracks and defects in the flux guiding magnets and parasitic air gaps in and directly around the magnetic circuit. Considering the high cost pressure, test systems must adapt to the increasing complexity of the components and detect defects completely in-situ. For these requirements the novel and nondestructive measurement system is suitable to monitor and assure the quality of magnetic actuators within the manufacturing process. The measuring principle is based on the characterization of the magnetic circuit according to the magnetic stray fields that can be quantified by magnetoelectronic GMR-elements outside the circuit. GMR sensors are particularly suited due to their measurement range and their linearity. Their measurement range coincides with the magnetic stray fields which were demonstrated by magnetic field simulation of electromagnetic actuators. © 2013 IEEE.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electromagnetic actuators; GMR-sensor; magnetic stray fields; nondestructive measurement system